Structural changes in the assets of Ukrainian enterprises under the transformation of goods and resources markets - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the formation of new scientific decisions on the study of the peculiarities of asset management in Ukrainian enterprises under the conditions of transforming goods and resource markets (global, international, and, in particular, national, sectoral, and regional). The scientific and practical necessity of intensifying the processes that increase the adaptability, flexibility, and efficiency of business in Ukraine through effective asset (property) management within the framework of transformational processes occurring in goods and resource markets has been revealed. The aim of the article is to identify ways to improve the efficiency of asset management in Ukrainian enterprises under the conditions of transforming goods and resource markets (global, international, and especially national, sectoral, and regional). Methodology: A set of general and specific methods has been applied at both empirical and theoretical levels. These include the method of literary analysis to study scientific issues in the field of asset management by business entities; the method of analysis to identify trends and features of managing assets (property) in general, and non-current and current assets in large, medium, small, and micro-enterprises in Ukraine; the method of synthesis to determine the problems of managing assets (property) in general, as well as non-current and current assets in large, medium, small, and micro-enterprises in Ukraine; the methods of induction and deduction to develop a set of recommendations for enhancing the adaptability, flexibility, and effectiveness of businesses in Ukraine in the context of asset (property) management in the context of the transformational processes that take place in goods and resource markets; and the methods of systematization, grouping, and logical generalization to organize information and formulate the conclusions and scientific proposals of the article. Results: ways to improve asset management efficiency in Ukrainian enterprises have been identified in the context of market transformations in goods and resources (global, international, and especially national, sectoral, and regional). JEL Classification: D21, L21, M13